Effects of implementation strategies aimed at improving high-value verification methods of nasogastric tube placement: A systematic review - Li, Jiamin; Sun, Xiangyu; Wu, Xinjuan (Frontiers in Nutrition, 2022)
Background X-ray and pH testing, which clinical practice guidelines have proven to be effective in determining nasogastric tube (NGT) placement, were named the high-value methods. Implementation strategies can help to integrate high-value methods into particular contexts. The aim of this systematic review was to summarize the evidence of implementation strategies aimed at improving high-value verification methods of NGT placement. Methods PubMed, ProQuest, and CINAHL were searched until June 2022. The Cochrane Effective Practice and Organization of Care (EPOC) taxonomy was used to categorize implementation strategies. Results The initial search identified 1,623 records. Of these, 64 full-text studies were reviewed. Finally, 12 studies were included and used for qualitative synthesis. Eleven studies used an education component as an implementation strategy. Only one study based their implementation strategy on a barriers and facilitators assessment. None of the studies reported enough detail of the implementation strategy used in their studies. Seven studies were eligible for inclusion in the meta-analysis. Three of these seven studies revealed a significant improvement of the high-value method after strategy implementation. As heterogeneity was present in the high level, the pooled effect estimated was not calculated. Conclusion Most studies used an implementation strategy with an educational component. Unfortunately, no conclusion can be drawn about which strategy is most effective for improving high-value verification methods of NGT placement due to a high level of heterogeneity and a lack of studies. We recommend that future studies fully connect their implementation strategies to influencing factors and better report the details of implementation strategies. Systematic review registration [www.crd.york.ac.uk/PROSPERO/], identifier [CRD42022349997].